Investigation of the Mechanisms of Tramadol-Induced Seizures in Overdose in the Rat - Camille Lagard; Dominique Vodovar; Lucie Chevillard; Jacques Callebert; Fabien Caillé; Géraldine Pottier; Hao Liang; Patricia Risède; Nicolas Tournier; Bruno Mégarbane (MDPI AG, 2022)
Tramadol overdose is frequently associated with the onset of seizures, usually considered as serotonin syndrome manifestations. Recently, the serotoninergic mechanism of tramadol-attributed seizures has been questioned. This study's aim was to identify the mechanisms involved in tramadol-induced seizures in overdose in rats. The investigations included (1) the effects of specific pretreatments on tramadol-induced seizure onset and brain monoamine concentrations, (2) the interaction between tramadol and γ-aminobutyric acid (GABA)A receptors in vivo in the brain using positron emission tomography (PET) imaging and 11C-flumazenil. Diazepam abolished tramadol-induced seizures, in contrast to naloxone, cyproheptadine and fexofenadine pretreatments. Despite seizure abolishment, diazepam significantly enhanced tramadol-induced increase in the brain serotonin (p < 0.01), histamine (p < 0.01), dopamine (p < 0.05) and norepinephrine (p < 0.05). No displacement of 11C-flumazenil brain kinetics was observed following tramadol administration in contrast to diazepam, suggesting that the observed interaction was not related to a competitive mechanism between tramadol and flumazenil at the benzodiazepine-binding site. Our findings do not support the involvement of serotoninergic, histaminergic, dopaminergic, norepinephrine or opioidergic pathways in tramadol-induced seizures in overdose, but they strongly suggest a tramadol-induced allosteric change of the benzodiazepine-binding site of GABAA receptors. Management of tramadol-poisoned patients should take into account that tramadol-induced seizures are mainly related to a GABAergic pathway.